Sistem Informasi Perencanaan Pembangunan Desa Berbasis Open Source WebGIS - Anggriawan Dwi Sartono; Anang Wahyu Sejati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In development planning activities, information disclosure is needed to prevent resistance from the community. With more and more people getting information, it has the potential to increase participation from the community. This study discusses the disclosure of information on village development planning in Klaten Regency. Klaten Regency was chosen as the research location because in disseminating information on village development planning, information technology has not been used. Submission of information only uses billboards that are installed in certain places with general and static information. This method is considered less effective in the midst of the development of information technology today. Therefore, this research provides a solution by creating a village development planning information system based on open source WebGIS. Making this information system is done by integrating spatial data with attribute data using open source software which is then visualized and disseminated in the form of WebGIS. The resulting system contains details information on development activities to physical realization and the budget used. In addition to functioning as a socialization medium, this information system also functions as a monitoring tool for ongoing development activities and as a digital archive that can be used as reference for future development plans.